Changes in morpho-physiological and yield attributes of Sesamum indicum under waterlogging at different growth stages (Journal of Bangladesh Academy of Sciences, 2022)
To understand the responsive nature to excess water, a pot experiment was conducted at different growth stages of sesame (Sesamum indicum L. cv. BARI Til-4). The waterlogging stress at each stage was set to three durations, viz. 2, 4, and 6 days. Twelve different treatment combinations were replicated three times and arranged in a completely randomized design. Different morpho-physiological and yield parameters were measured after the completion of the longest stress duration (6 days). The data revealed that sesame is vulnerable to excess water conditions, and the sensitivity is positively correlated with the stress duration. Plant biomass, leaf area, SPAD value, and the yield attributes recorded are observed to be declined with the increment of stress duration. Another important finding is that among the three growth stages of sesame, the reproductive stage is the most sensitive stage, which hardly withstands waterlogging. the stress at the vegetative stage affect yield parameters minimally.J. Bangladesh Acad. Sci. 46(2); 165-173: December 2022